Analisis Literasi Sains Siswa Kelas VB SD Pada Mata Pelajaran IPAS Materi Organ Pernapasan Manusia - Erzania Maulida, Hanifa; Ardi Saputro, Bagus; Stelladiba Cindy Ayu, Angela Astrid; Roshayanti, Fenny (UNIB Press, 2024)
The era of rapid progress in science and technology (IPTEK) has of course also had an influence on the development of the world of education. One of the developments in science that can contribute is science education. Science education is a learning process that emphasizes providing direct experience to develop competencies to explore and understand the natural environment scientifically. Scientific literacy ability in Indonesia is still relatively low based on data from the PISA study. Scientific literacy ability is an average of 396 and is still ranked 70th out of 78 participants. This research is a qualitative descriptive research. The sample in this study was 28 VB class students. The research sampling technique is purposive sampling. The attitude aspect of the scientific literacy profile is in the medium category, this can be seen from the students' answers to the questionnaire that has been given. This is also supported by the class teacher's interview which stated that scientific literacy in the VB class had never been carried out, scientific literacy was only carried out during practicum in science and science learning.